Stropharia daliensis sp. nov. (Strophariaceae, Agaricales) from Yunnan Province, China - Feng, Yunli; Fang, Yuan; Liu, Shaoxiong; Guo, Xiang; Luo, Xi; Gao, Zhanghui; Ma, Ming; Hua, Rong; Sun, Dafeng (Phytotaxa, 2025)
Stropharia daliensis sp. nov., collected from Dali, Yunnan, China, is proposed based on morphological and molecular analyses. It is characterized by its viscid to glutinous basidiomata, light reddish-brown to reddish-orange pileus covered with white to light yellow squamules, stipe evanescent annulus in the upper part of the stipe, below the annulus densely covered light yellow triangular squamules, acanthocytes absent. Phylogenetic analysis of the ITS and nrLSU confirmed the phylogenetic placement of the new species. A comprehensive description, line drawings of microstructures, and comparisons with morphologically similar species are provided in this paper.